An Analysis of Service Quality at the Palu City Branch of Badan Penyelenggara Jaminan Sosial Health - Cheko Farah; Ira Nuriya Santi; Maskuri Sutomo; Farid Farid (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the quality of public services at the Badan Penyelenggara Jaminan Sosial (BPJS) Health Office of Palu City based on five dimensions of service quality. Research Methodology: This study employed a qualitative method with a descriptive approach. Data were collected through direct observation and in-depth interviews with BPJS Health employees and service participants at the BPJS Health Office of Palu City. The data were analyzed using qualitative descriptive techniques to capture participants’ perceptions of service performance. Results: The findings show that the five dimensions of service quality tangibles, empathy, reliability, responsiveness, and assurance are categorized as good. Among these dimensions, reliability is the strongest aspect, indicating that BPJS Health employees provide services accurately, consistently, and responsibly. Public satisfaction with the services is also categorized as good. Conclusions: This study concludes that the overall quality of public services at the BPJS Health Office of Palu City is good and effective in meeting community expectations. Nevertheless, continuous improvement is still required, particularly in strengthening service-supporting infrastructure. Limitations: This study was limited to a single BPJS branch office; therefore, the findings cannot be generalized to all BPJS Health offices in Indonesia. Contributions: This study provides empirical evidence on the implementation of service quality in public health insurance services and can serve as a reference for improving infrastructure and strengthening employee reliability to enhance public service performance.